Pneumonia and Covid-19 Prediction using CNN - Dr. V.Vinodhini; C.S.Charan; A.Deepa (International Journal of Engineering and Management Research, 2023)
Convolutional Neural Network (CNN) is used to automatically process large amounts of medical images, and to identify complex associations for disease diagnosis. An automatic diagnostic system has been developed using Convolutional Neural Network (CNN) which uses chest X-ray results to diagnose whether a person is affected by Pneumonia or COVID-19. It also determines the type of Pneumonia along with the newly discovered COVID-19. The diagnostic deep learning method uses computed tomography (CT) images, chest X-rays to classify Pneumonia, types of Pneumonia and COVID-19.